Analysis of New Media Literacy In Message Reception @Aboutcirebon For Generation Z - Dian Nita Aryani; Farida Nurfalah (Athena: Journal of Social, Culture and Society, 2026)
The rapid development of digital technology has changed the way Generation Z obtains information. This study aims to analyze how Generation Z receives messages from the Instagram account @AboutCirebon and how they assess the credibility of the content shared. The study uses a descriptive qualitative method with seven Generation Z informants, who actively follow the @AboutCirebon account, interviewed in depth to collect data, supplemented by observation and content documentation. The results show that Generation Z cognitively relies on visual aspects without comprehensive supervision. The emotional dimension reveals impulsive reactions triggered by pride in local culture and dissatisfaction with public issues. Aesthetic appreciation of visual content is high, while educational value is neglected. Moral awareness of social media interactions is not yet deep, with informants aged between seventeen and twenty-one years old receiving messages simply as entertainment. Generation Z often assesses the credibility of content with quick decisions such as account reputation and local context relevance. However, additional confirmation from other sources is rarely done. New media literacy needs to be strengthened through collaboration between local media, educational institutions, and the government to encourage critical, ethical, and responsible media consumption among Generation Z.